Net income of provincial and territorial liquor authorities and government revenue from the control and sale of alcoholic beverages, fiscal years ended March 31 - Statistics Canada (Government of Canada, 2017)
This table contains 180 series, with data for years 1993 - 31-MAR-13 not all combinations necessarily have data for all years), and was last released on 2015-05-04. This table contains data described by the following dimensions (Not all combinations are available): Geography (15 items: Canada;Newfoundland and Labrador;Nova Scotia;Prince Edward Island ...), Liquor authorities (12 items: Gross sales (including Goods and Services Tax (GST));Deduct: Goods and Services Tax (GST);Net sales;Deduct: cost of goods sold ...).